Human Resource Empowerment Viewed from the Perspective of Education, Experience, Skills, Security using Fishbone Analysis (Case Study of Grocery Traders in Pati Regency) - Yuningtyas Kartikawati; Supriyono; Sunarno (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the empowerment of human resources in terms of the perspective of education, experience, skills, safety for grocery traders in Pati Regency. This type of research is qualitative by using fishbone analysis. The research sample was 5 informants (informants) who were selected based on holding positions for more than 2 years, having sufficient time to be interviewed and willing to become informants. Data were collected by interviews and analyzed qualitatively using the fishbone method (cause and effect). The results obtained from the Empowerment of Human Resources from an educational perspective include education levels, knowledge of information technology, written communication, and knowledge of human resource development.